2002
DOI: 10.1002/jemt.10190
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in peripheral arterial chemoreceptors

Abstract: The peripheral arterial chemoreceptors of the carotid body participate in the ventilatory responses to hypoxia and hypercapnia, the arousal responses to asphyxial apnea, and the acclimatization to high altitude. In response to an excitatory stimuli, glomus cells in the carotid body depolarize, their intracellular calcium levels rise, and neurotransmitters are released from them. Neurotransmitters then bind to autoreceptors on glomus cells and postsynaptic receptors on chemoafferents of the carotid sinus nerve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 148 publications
(180 reference statements)
2
60
0
10
Order By: Relevance
“…Compared to normoxia, hyperoxia caused a decrease in cAMP in the CB in all ages. Adenosine effects via A 2 receptors, which are known to be expressed in the CB (Gauda 2002), can represent one of the mechanisms maintaining high cAMP levels in hypoxia. It is worth noting that the release of adenosine in the CB is maximal at mild levels of hypoxia (10%O 2 ), decreasing with higher intensities of hypoxic stimulation and that the most intense hypoxia used in this study does not increase the release of adenosine in the SCG or CA (Conde and Monteiro 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to normoxia, hyperoxia caused a decrease in cAMP in the CB in all ages. Adenosine effects via A 2 receptors, which are known to be expressed in the CB (Gauda 2002), can represent one of the mechanisms maintaining high cAMP levels in hypoxia. It is worth noting that the release of adenosine in the CB is maximal at mild levels of hypoxia (10%O 2 ), decreasing with higher intensities of hypoxic stimulation and that the most intense hypoxia used in this study does not increase the release of adenosine in the SCG or CA (Conde and Monteiro 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Of course adenosine is not the only modulator of cAMP levels in the CB, as it is well known that hypoxia also increases the release of many other neurotransmitters, particularly dopamine (Vicario et al 2000). It is also known that the CB expresses high levels of D 2 dopamine receptors (Gauda 2002) which are negatively coupled to adenylate cyclase (Kebabian and Calne 1979). In fact, it would appear that the much higher rate of dopamine release in the rat vs. the rabbit CB in hypoxia (Vicario et al 2000) could explain the inability of hypoxia to increase the cAMP levels in the rat CB above those found in normoxia, as it has been previously observed in the rabbit (Cachero et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was designed to work with freshly isolated intact CBs to avoid potential phenotypic changes of simplified preparations such as primary tissue cultures (Gauda, 2002;Conde et al, 2007). We have selected a fingerprinting method to measure ROS production, i.e., E GSH , because it is a reliable method (Schafer and Buettner, 2001) free of the uncertainties derived of the use of fluorescent indicators (Moudgil et al, 2005;Waypa and Schumacker, 2005).Rotenone was tested at three different concentrations in the diaphragm to assess E GSH and in the CB to assess the effect on the chemoreceptor activity (release of 3 H-CA), and in both tissues, in the absence and in the presence of the antioxidant NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is reported that dopamine D 2 receptor mRNA is expressed in glomus cells of rat carotid body in a study using ISH (Czyzyk-Krzeska et al 1992b), and that immunoreactivity for dopamine D 2 receptor was observed in glomus cells and nerve fiber of human carotid body (Lazarov et al 2009). On the other hand, it is suggested, again using ISH, that dopamine D 1 receptor is absent in glomus cells because dopamine D 1 receptor mRNA was not detected in glomus cells of rat carotid body (Czyzyk-Krzeska et al 1992b;Gauda 2002). Physiological and pharmacological reports indicate that dopamine is an inhibitory neurotransmitter in almost all species (Fidone et al 1982;Gonzalez et al 1994;Iturriaga and Alcayaga 2004).…”
mentioning
confidence: 99%